Synthesis, Characterization, and Study of Proton Exchange Polymer Membrane Properties of Sulfonated Copolymer Eugenol-diallyl Phthalate - Ngadiwiyana Ngadiwiyana; Nor Basid Adiwibawa Prasetya; Gunawan Gunawan; Tutuk Djoko Kusworo; Heru Susanto (Indonesian Journal of Chemistry, 2021)
Synthesis biopolymer of sulfonated copolymer eugenol-diallyl phthalate (PEGDAF), its characterization, and study of proton exchange polymer membrane properties had been done. This synthesis was conducted by eugenol and diallyl phthalate reaction to form PEGDAF, which is sulfonated using sulfuric acid. In addition, the functional groups of the PEGDAF and its sulfonated form were analyzed using FT-IR. Furthermore, the polymer properties were determined by measuring values of sulfonation degree, cation exchange capacity, proton conductivity, and water uptake. FT-IR spectra showed that the vinyl group had been added to the process of PEGDAF formation, while spectra deconvolution was used to confirm the occurrence of sulfonation reaction. The sulfonation of PEGDAF in 2 h optimum reaction time produces a black solid with a melting point of 133 °C in 16.55% yield. The highest proton conductivity, cation exchange capacity (CEC), and water uptake were 8.334 × 10–6 S cm–1, 0.44 meq/g, and 73.0%, respectively.